Addressing Unresolved Complex Mixture of I/SVOCs Emitted From Incomplete Combustion of Solid Fuels by Nontarget Analysis. Issue 23 (1st December 2021) - Huo, Yaoqiang; Guo, Zihua; Liu, Yuzhe; Wu, Di; Ding, Xiang; Zhao, Zhijun; Wu, Manman; Wang, Lin; Feng, Yanli; Chen, Yingjun; Wang, Shuxiao; Li, Qing; et al.
Abstract: The major fraction of intermediate and semi‐volatility organic compounds (I/SVOCs) is still unresolved by traditional analyses, leaving large unresolved complex mixture (UCM) and limiting the estimation of secondary organic aerosol (SOA). This study addressed the UCM by employing two‐dimensional gas chromatography−time‐of‐flight mass spectrometry. The ratios of UCM in I/SVOCs emitted from household burning of biomass and coal were reduced to 1.0 ± 0.3% and 2.1 ± 2.0%, respectively, and these levels are one order of magnitude less than those reported in previous studies. Phenols, polycyclic aromatic hydrocarbons, and ketones made the major contribution to I/SVOCs emission factors (EFs) (65.9 ± 9.6%) for biomass burning, while amides, acids, and esters constituted the majority of EFs (56.5 ± 45.0%) for coal burning. Furthermore, SOA production can be predicted via the highly identified I/SVOCs compounds based on volatility distributions of each speciated species. These majority compounds contribute the predicted SOA production with 76.0 ± 12.7% and 82.0 ± 60.3% for biomass and coal burning, respectively. Underestimated SOA production with the ratio of 62.5 ± 25.2% to 80.9 ± 2.8% via previous Bins method has been well addressed. The obtained results suggest that the nontarget analysis can significantly improve the accuracy of I/SVOCs estimation and environmental impacts by addressing chemical components at the molecular level. Plain Language Summary: Intermediate and semi‐volatility organic compounds (I/SVOCs) have already been recognized as important precursors of secondary organic aerosol in the atmosphere and are harmful to human health. Their major chemical components still constitute a largely unresolved complex mixture. This knowledge gap in chemical analysis limits further understanding of the environmental impacts of I/SVOCs, including estimates of secondary organic aerosol produced. This study addressed the chemical complexity of unresolved complex mixture by employing two‐dimensional gas chromatography−time‐of‐flight mass spectrometry. Many unresolved complex mixtures in I/SVOCs were effectively identified by the nontarget analysis. Furthermore, secondary organic aerosol production can be predicted via the highly identified I/SVOCs compounds based on their volatility distributions, which were obtained from comprehensive analyses of I/SVOCs. These results suggest that the nontarget analysis developed herein significantly improves the I/SVOCs estimates used in identifying chemical compounds at the molecular level and environmental impacts. Key Points: The unresolved ratios of intermediate and semi‐volatility organic compounds emitted from household biomass and coal burning are reduced to about 1.0% and 2.1%, respectively The predictions of secondary organic aerosol production are increased by 62.5%–80.9% using non‐target analysis method, as compared with traditional 1D‐GC‐MS The improvement in identifying intermediate and semi‐volatility organic compounds species benefits the impact estimation of source emissions on the atmospheric environment